Free and total cortisol levels as predictors of severity and outcome in community-acquired pneumonia. - Christ-Crain, M; Stolz, D; Jutla, S; Couppis, O; Müller, C; Bingisser, R; Schuetz, P; Tamm, M; Edwards, R; Müller, B; Grossman, AB (2007)
RATIONALE: High cortisol levels are of prognostic value in sepsis. The predictive value of cortisol in pneumonia is unknown. Routinely available assays measure serum total cortisol (TC) and not free cortisol (FC). Whether FC concentrations better reflect outcome is uncertain. OBJECTIVES: To investigate the predictive value of TC and FC in community-acquired pneumonia (CAP). METHODS: Preplanned subanalysis of a prospective intervention study in 278 patients presenting to the emergency department with CAP. MEASUREMENTS AND MAIN RESULTS: TC, FC, procalcitonin, C-reactive protein, leukocytes, clinical variables, and the pneumonia severity index (PSI) were measured. The major outcome measures were PSI and survival. TC and FC, but not C-reactive protein or leukocytes, increased with increasing severity of CAP according to the PSI (P < 0.001). TC and FC levels on presentation in patients who died during follow-up were significantly higher as compared with levels in survivors. In a receiver operating characteristic analysis to predict survival, the area under the receiver operating characteristic curve (AUC) was 0.76 (95% confidence interval, 0.70-0.81) for TC and 0.69 (0.63-0.74) for FC. This was similar to the AUC of the PSI (0.76 [0.70-0.81]), and better as compared with C-reactive protein, procalcitonin, or leukocytes. In univariate analysis, only TC, FC, and the PSI were predictors of death. In multivariate analysis, the predictive potential of TC equaled the prognostic power of PSI points. CONCLUSIONS: Cortisol levels are predictors of severity and outcome in CAP to a similar extent to the PSI, and are better than routinely measured laboratory parameters. In CAP, the prognostic accuracy of FC is not superior to TC. Clinical trial registered with www.controlled-trials.com (ISRCTN04176397).